Colorectal Cancer: Epidemiological Trends, Screening, and Inheritability - Isabela Andhika Paramita; Hasan Maulahela; Kevin Winston (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2018)
Colorectal cancer is one of the most common cancer worldwide. The incidence and mortality trend in different areas of the world varies. Colorectal cancer incidence and mortality are increasing in some countries. There are also epidemiological shift towards younger age  (below 40). Most common non-invasive screening tests are fecal immunochemistry test (FIT) and fecal occult blood test (FOBT). Both have good sensitivity. The best invasive method for colorectal screening is still colonoscopy. Hereditary colorectal cancer is an important factor in younger age colorectal cancer. Familial adenomatous polyposis and Lynch syndrome are most common hereditary CRC. In familial or hereditary CRC, the chance of developing the cancerous form of the disease is nearly inevitable. Genetic testing may benefit the patients and their future progenies.